Cameroon : Staff Report for the 2009 Article IV Consultation and Request for disbursement Under the Rapid-Access Component of the Exogenous Shocks Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses a request from Cameroon for Disbursement Under the Rapid-Access Component of the Exogenous Shocks Facility (RAC-ESF). Despite improvements, the economy of Cameroon remains vulnerable to commodity shocks, especially from oil; and reducing poverty is a challenge. The authorities are eager to set the economy on a higher-growth path that can lower poverty. IMF staff welcomes the accelerated implementation of structural measures to increase the economy's resilience to shocks. IMF staff supports the authorities' request for the rapid-access component of the ESF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet